Tool for rapid transient transpiration cooled re-entry simulation - Hermann, T; Naved, I; McGilvray, M (American Institute of Aeronautics and Astronautics, 2019)
This Paper presents a numerical model intended for a system study of transpiration-cooled thermal protection systems. The code PIRATE enables rapid transient calculations for thermal protection systems of hypersonic flight vehicles. In the code, semi-empirical aerodynamic correlations are employed. However, the code could also be used by applying higher-fidelity inputs from computational fluid dynamics calculations for more complicated vehicle geometries. The wall temperature distribution is calculated by using the thermal impulse and step responses of porous media, increasing the calculation speed significantly. A heat flux balance is considered for a one-dimensional porous material. The code is validated with experimental data of plasma wind tunnel tests and the SHEFEX II flight experiment. The transient heating of a flat plate model in a steady-state flow condition in the Arc-heated wind tunnel 2 (L2 K) plasma wind tunnel is assessed for both uncooled and transpiration-cooled cases. The SHEFEX II flight simulation accounts for transient external flow conditions and is used to assess the downstream coolant film effect after the injection point. The trends of experimental temperature measurements are replicated well by the simulations. The predicted and measured temperatures are in good agreement and within a margin of 10% with maximum deviations of 40 K.